The Influence of Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), and Operating Costs Operating Income (BOPO) on Profitability in Banks Listed on the Indonesia Stock Exchange for the 2016-2018 Period - Cindy Cuaca; Ingot Simangunsong; Arifah Maharani; Ike Rukmana Sari (Kusuma Negara Business School, 2020)
This study aims to analyze the effect of Capital Adequacy Ratio (CAR), Non-Performing Loan (NPL), and Operational Cost of Operating Income (BOPO) on Profitability (ROA). The data used in this study were obtained from the annual published financial reports of banks listed on the Indonesia Stock Exchange for the 2016-2018 period. The sampling technique used was a sample size of 33 commercial banks listed on the Indonesia Stock Exchange (BEI) for the period 2016–2018. The analysis technique used is statistical test with multiple regression methods and hypothesis testing using the F test and T test which previously had been done with the classical assumption test first. The results showed that simultaneously the Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), and Operating Costs Operating Income (BOPO) had a significant effect on Return on Assets (ROA) in banking companies on the IDX for the 2016-2018 period. Partially, the variable Capital Adequacy Ratio (CAR) has no and insignificant effect on Return on Assets (ROA). The Non Performing Loan (NPL) variable has no and insignificant effect on Return on Assets (ROA). Operational Cost Variable Operating Income (BOPO) has a significant effect on Return on Assets (ROA). From this study, the coefficient of determination (R2) was 0.746; this means that 74.6% of the Return on Assets (ROA) variable can be explained by the independent variables, namely Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), and Operational Costs. Operating Income (BOPO), and the remaining 25.4% is explained by other variables outside the equation.